New Readings of Husseini Renaissance Narrations - Yasmine Hatem Badeed Al Ibrahimi , Lect. (lark, 2021)
Being the focus of all levels and religions, the Husseini renaissance has received great attention from all writers and researchers as well. No historical event has received that status as this renaissance since its establishment up to now.  Husseini's renaissance represents the divine line vis-à-vis the material Umayyad line. The current study shows that Al-Hussein's goals have been achieved. His principles come out at the end, no matter how much enemies try to deform reality.  Once reading Hussainiya's renaissance, it can be noticed that it has been planned from the very beginning when he has marched from Medina to Mecca. To be chosen by God, his death sparkles the feeling of total submission to God's instructions.Despite all the attempts of the Umayyad and Abbasid state and their writers and narrators, who made their best efforts to fabricate truths and convey a false perception of every position that al-Husayn (peace be upon him) or his leaders and supporters endowed, and even fabricated his movements, Therefore, when one read any murder or historical book that included that dark period, it is found that history writers put Hussein (peace be upon him) in a framework of not being able to choose his messenger and leaders and that he was confused in his steps, and he took advantage of his religious position in controlling the convoys to finance his renaissance, so they faked all positions and steps were taken by writers and historians, they took their surrender, without paying attention to the extent of forgery that took place in this Hussainiya divine renaissance, which the Great Prophet relied on to revive and perpetuate Islam.
Keywords: Ali bin Abi Talib (PBUH), Hassan bin Ali (PBUH), Hussein bin Ali (PBUH), Muawiyah bin Abi Sufyan, Yazid bin Muawiyah